The effect of cocoa clones on chocolate flavour - Abd. Samah, Othman; Suratman, Jumali; Wan Ibrahim, Wan Aidah (2010)
Fermentation of Theobroma cacao L. beans has been considered to be the most important factor influencing cocoa flavour and has accordingly received most attention. Five selected cocoa clones (KKM 1, KKM 22, PBC 123, PBC 140 and BR 25) choosen from major cocoa plantations in Malaysia were treated under normal fermentation process. Samples were prepared in the prescribed techniques to evaluate chocolate flavour, respectively. The present of foreign taste was detected in all five samples, with the PBC 123 being significantly higher than the rest at p<0.05 while PBC 140 has the lowest foreign taste. Chocolate made of PBC 140 clone was highest in acceptability, which significantly different from the rest at p<0.05. PBC 123 on the other hand was the least acceptable. The most acceptable sample was the reference sample. In general PBC 140 was the best clone evaluated in this study in terms of sensory evaluation as compared to the other four samples and also to other previously studies using various strategies on fermentation techniques including those which used pure cultures of selected microbes for fermentation.